2021
DOI: 10.1111/dmcn.14913
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in adults with cerebral palsy: a modifiable risk factor for cardiovascular disease prevention

Abstract: Aim To assess diet quality and its relationship with cardiovascular health measures for adults with cerebral palsy (CP). Method A convenience sample of 45 adults with CP (26 females, 19 males; mean age 35y 10mo [SD 14y 9mo]). were recruited for this cross‐sectional study. Demographic, medical, and Gross Motor Function Classification System (GMFCS) information were obtained through in‐person visits. Participants completed two 24‐hour dietary recalls using the Automated Self‐Administered 24‐hour Dietary Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…9 Overweight and obesity could be risk factors for cardiovascular disease in adults with CP. 28 We found that overweight and obesity were more common in adults in EDACS levels I and II compared to adults in EDACS levels III to V. The mean BMI of 24 for the whole cohort was substantially lower than the BMI of 29.1 reported for adults with CP in the US. 29 Even so, the risk of cardiovascular disease is substantially higher in adults with CP compared to the general population and needs to be considered.…”
Section: Discussioncontrasting
confidence: 52%
“…9 Overweight and obesity could be risk factors for cardiovascular disease in adults with CP. 28 We found that overweight and obesity were more common in adults in EDACS levels I and II compared to adults in EDACS levels III to V. The mean BMI of 24 for the whole cohort was substantially lower than the BMI of 29.1 reported for adults with CP in the US. 29 Even so, the risk of cardiovascular disease is substantially higher in adults with CP compared to the general population and needs to be considered.…”
Section: Discussioncontrasting
confidence: 52%
“…Low WG intake is probably one of the most important but easiest-to-be-ignored factors. With the literature review, we found more and more researchers have noticed the impact of WGs on CVD and the association between CVD and WG intake [ 13 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, few studies have focused on a comprehensive analysis of the long-term trend of CVD mortality attributable to low WG intake in China.…”
Section: Discussionmentioning
confidence: 99%
“…A newly published prospective study based on a long-running birth cohort study in Australia also concluded the same result [ 22 ]. Active ingredients in whole grains, such as dietary fiber, vitamins, minerals, antioxidants, lingams, phytosterols, etc., can affect cardiovascular health through the metabolism of sugar, blood lipids, lipoproteins, and vascular endothelial function [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited to participate in a study evaluating activity levels, nutrition, and the impact of these factors on the health of adolescents and adults with CP. This population has been described previously 31‐33 . Data for the current project are from a subset of the measures obtained in the parent study.…”
Section: Methodsmentioning
confidence: 99%
“…This population has been described previously. [31][32][33] Data for the current project are from a subset of the measures obtained in the parent study.…”
Section: Methodsmentioning
confidence: 99%